CXCL12 and eotaxin are independent prognostic serum biomarkers in gastric cancer - Brodkin, Jefim; Kaprio, Tuomas; Mustonen, Harri; Leppä, Alli; Kokkola, Arto; Salmi, Marko; Jalkanen, Sirpa; Haglund, Caj; Böckelman, Camilla (Springer Nature, 2026)
Gastric cancer is the fifth most common cancer and the fifth leading cause of cancer-related death worldwide. Its poor prognosis primarily results from a late diagnosis and the lack of effective treatments for advanced disease. Thus, we aimed to identify new prognostic serum biomarkers to aid clinical decision-making. Our patient cohort consisted of 240 individuals who underwent surgery for histologically verified gastric adenocarcinoma in the Department of Surgery at Helsinki University Hospital between 2000 and 2009. To determine the serum protein concentrations of cytokines and growth factors, we utilized Bio-Rad’s premixed Bio-Plex Pro Human Cytokine 27- and 21-plex assay kits. Among the 48 biomarkers we analyzed, three emerged as statistically significant prognostic markers for disease-specific survival using the Cox proportional hazards univariate analysis: C-X-C motif chemokine ligand 12 (CXCL12) (hazard ratio [HR] 0.39, 95% confidence interval [CI] 0.23–0.63, p < 0.001), stem cell factor (HR 0.38, 95% CI 0.19–0.77, p = 0.007), and eotaxin (HR 0.57, 95% CI 0.37–0.89, p = 0.013). Our multivariate survival analysis revealed that, among the 48 biomarkers analyzed, CXCL12 and eotaxin served as independent prognostic markers among gastric cancer patients. The prognostic effect of inflammatory serum biomarkers in gastric cancer may provide new insights into the immunological microenvironment of disease.